Manajemen Atonia Uteri - Rafialdi Fatwaddin, Muhammad; Assauri, Sopyan; Nurul Milenia, Uni (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background: Uterine atony is one of the post-partum bleeding that can cause death in the mother. Uterine atony is an obstetric emergency and is one of the top five causes of maternal death. Post-partum/post-partum bleeding (PPH) is bleeding that occurs after delivery. Uterine atony is the 5th cause of maternal death. Method: The source search was carried out on the online portal of journal publications as many as 16 sources from MedScape, Google Scholar and the Nation Center for Biotechnology Information / NCBI with the keywords "uterine atony" and “postpartum hemorrhage”. Discussion: Bleeding in uterine atony occurs during the third stage of labor, where after the delivery of the placenta the myometrial muscles should contract to constrict the arteries and stop bleeding at the placental implantation site. Management of the third stage is an important stage in labor that plays a role in preventing post-partum bleeding. Conclusion: Uterine atony can be diagnosed when there is more blood loss than usual and a flaccid and enlarged uterus. Active management of the third stage is a way to prevent uterine atony.